Adapting Palabe folk tales into multimodal literacy for early childhood education - Indhra, Feerlie Moonthana; Anshori, Muhammad; Solihin, Muhammad (Indonesian Journal of Educational Development (IJED), 2025)
This study examines the urgency of adapting Palabe, an oral literature from the Bungo community in Jambi Province, into multimodal literacy resources for early childhood education. Palabe is at risk of extinction due to limited documentation, reduced oral transmission, and declining interest among younger generations. Yet, Palabe contains significant moral, social, and religious values that align with national character education goals. A qualitative descriptive method with a content analysis approach was applied, grounded in Early Literacy theory. Data were obtained from 23 Palabe narratives collected from 12 participants (7 males and 5 females) across eight sub-districts in Bungo Regency, selected purposively for their cultural expertise and involvement in oral tradition. Data collection included participatory observation, oral recording, transcription, and documentation. Findings show that 12 Palabe stories possess high educational values, including patience, collaboration, sincerity, perseverance, and trust in God. However, these stories require adaptation to be developmentally appropriate for children aged 5–6 years. The adaptation process involves simplifying sentences, adding repetition, shortening plots, and integrating visual illustrations to enhance comprehension and engagement. The study recommends incorporating adapted Palabe into early childhood curricula and developing illustrated storybooks to preserve cultural identity, foster literacy, and strengthen character education through enjoyable, meaningful learning.